2014
DOI: 10.1371/journal.pone.0098946
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of cGMP-Dependent Protein Kinase Type I in Intact Cells Is Independent of N-Terminal Autophosphorylation

Abstract: Although cGMP-dependent protein kinase type I (cGKI) is an important mediator of cGMP signaling and upcoming drug target, its in vivo-biochemistry is not well understood. Many studies showed that purified cGKI autophosphorylates multiple sites at its N-terminus. Autophosphorylation might be involved in kinase activation, but it is unclear whether this happens also in intact cells. To study cGKI autophosphorylation in vitro and in vivo, we have generated phospho-specific antisera against major in vitro-autophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…In addition, it is unknown why the mutant enzymes undergo more rapid autophosphorylation in vitro than the WT enzymes; the mutation may release the enzyme's phosphotransfer activity without reducing the catalytic cleft's access to the autoinhibitory loop (where the autophosphorylation sites are located). Consistent with our results indicating a lack of autophosphorylation in intact cells, Vallur et al could not detect PKG1a/PKG1b autophosphorylation in a number of cell types using phospho-specific antibodies (28). It has been hypothesized that PKG1 autophosphorylation leads to sustained PKG1 signaling after cellular cGMP levels fall (29); however, our findings, combined with those of Vallur et al, cast doubt on the physiological significance of PKG1 autophosphorylation.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, it is unknown why the mutant enzymes undergo more rapid autophosphorylation in vitro than the WT enzymes; the mutation may release the enzyme's phosphotransfer activity without reducing the catalytic cleft's access to the autoinhibitory loop (where the autophosphorylation sites are located). Consistent with our results indicating a lack of autophosphorylation in intact cells, Vallur et al could not detect PKG1a/PKG1b autophosphorylation in a number of cell types using phospho-specific antibodies (28). It has been hypothesized that PKG1 autophosphorylation leads to sustained PKG1 signaling after cellular cGMP levels fall (29); however, our findings, combined with those of Vallur et al, cast doubt on the physiological significance of PKG1 autophosphorylation.…”
Section: Discussionsupporting
confidence: 86%
“…For the present study, the obtained antisera were affinity purified as described previously. 48 Blots were scanned using a fluorescence scanner (Odyssey, LI-COR Biosciences, Lincoln, NE) after incubation with a secondary fluorescent donkey anti-rabbit antibody labelled with IRDye 800CW (LI-COR Biosciences, Lincoln, NE) for 1 hour, at 4 C, in a 1:20,000 dilution. To test specificity of the obtained bands, the blots were probed with the primary antibody, which was pretreated with the blocking peptide, overnight, or the secondary antibody only.…”
Section: Western Blotsmentioning
confidence: 99%
“…determined that N‐terminal phosphorylation, while readily inducible in vitro, is not required for catalytic activity of PKG in intact cardiac myocytes. Using antiphospho antibodies specific to pThr59 and pThr85, they showed that PKG phosphorylation at these sites was not detected in vivo under basal and PKG‐stimulated conditions . These findings suggest that under in vitro conditions with purified protein or cell extract PKG autophosphorylation is preferred over phosphorylation of other substrates, but under in vivo conditions the reciprocal effect seems to be preferred.…”
Section: Structure Localization and Ptms Of Pkgmentioning
confidence: 99%
“…These findings suggest that under in vitro conditions with purified protein or cell extract PKG autophosphorylation is preferred over phosphorylation of other substrates, but under in vivo conditions the reciprocal effect seems to be preferred. This may be due to the local environment and localization of PKG in vivo as well as interactions with other protein substrates that may not occur in vitro . However, this has yet to be extensively investigated.…”
Section: Structure Localization and Ptms Of Pkgmentioning
confidence: 99%